Optimizing Antimicrobial Dosing for Critically Ill Patients with MRSA Infections: A New Paradigm for Improving Efficacy during Continuous Renal Replacement Therapy - Jiaojiao Chen; Sihan Li; Quanfang Wang; Chuhui Wang; Yulan Qiu; Luting Yang; Ruiying Han; Qian Du; Lei Chen; Yalin Dong; Taotao Wang (MDPI AG, 2022)
The dosage regimen of vancomycin, teicoplanin and daptomycin remains controversial for critically ill patients undergoing continuous renal replacement therapy (CRRT). Monte Carlo simulation was applied to identify the optimal regimens of antimicrobial agents in patients with methicillin-resistant Staphylococcus aureus (MRSA) infections based on the mechanisms of different CRRT modalities on drug clearance. The optimal vancomycin dosage for patients received a CRRT doses ≤ 30 mL/kg/h was 20 mg/kg loading dose followed by 500 mg every 8 h, while 1 g every 12 h was appropriate when 35 mL/kg/h was prescribed. The optimal teicoplanin dosage under a CRRT dose ≤ 25 mL/kg/h was four loading doses of 10 mg/kg every 12 h followed by 10 mg/kg every 48 h, 8 mg/kg every 24 h and 6 mg/kg every 24 h for continuous veno-venous hemofiltration, continuous veno-venous hemodialysis and continuous veno-venous hemodiafiltration, respectively. When the CRRT dose increased to 30-35 mL/kg/h, the teicoplanin dosage should be increased by 30%. The recommended regimen for daptomycin was 6-8 mg/kg every 24 h under a CRRT dose ≤ 25 mL/kg/h, while 8-10 mg/kg every 24 h was optimal under 30-35 mg/kg/h. The CRRT dose has an impact on probability of target attainment and CRRT modality only influences teicoplanin.